Chemical dissolution of indium arsenide in the Br₂-HBr solutions - Tomashik, Z.F.; Danylenko, S.G.; Tomashik, V.N.; Kravetski, M.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The nature and kinetics of InAs chemical dissolution and chemical cutting, in the bromine solutions in hydrobromic acid have been investigated. It was shown that at low (up to 6 vol.%) bromine concentrations the InAs dissolution rate grows linearly with bromine concentration. Such solutions may be used to chemically polish InAs. Solutions containing from 20 to 30 vol.% Br₂ in HBr dissolve InAs with the rate 25 to 50 µ/min forming polished surfaces with etch pits. Such solutions may be used to chemically cut indium arsenide.